Pengaruh Pelaksanaan Baby gym terhadap Perkembangan Bayi - Syuhrotut Taufiqoh (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Infancy is a critical period that requires stimulation to stimulate growth and development—one of the efforts to stimulate the baby’s development. This study aims to determine the effect of implementing a baby gym on baby development in the Jagir Health Center, Surabaya, working area.Methods: This research was conducted in March 2020. This study uses a quasi-experimental approach with "Pretest-Post test with Control Group Design. The population in this study were infants aged 4–12 months who met the inclusion criteria. The selection of 134 babies resulted in a sample of 32 respondents, divided into 16 babies in the intervention group and 16 in the control group. They were collecting independent data using a checklist observation and dependent data by observing with DDST. The analysis used was a t-test on the sample and one free sample test with a P level <0.05.Results: There is an influence on the baby gym and gross motor development of babies who practice and do not practice using the t-test. Test results p = 0.000. There is an influence on the fine motor development of infants who practice and do not practice using the t-test. The test results in P = 0.001, meaning there is a difference between gross and fine motor development in the post-test intervention group and the control group with a p-value = 0.000.Conclusion: This study concludes that there is an effect of implementing a baby gym on the gross and fine motor development of infants. There is a need for socialization regarding guidelines and instructions for baby gym procedures in every health service so that they can be applied in stimulating children's motoric development.